Uniqueness of STFT Phase Retrieval for Bandlimited Vector Functions. (12th March 2023) - Zhang, Qingyue; Guo, Zhenli; Liu, Bei; Li, Rui
Abstract: In the article, we consider the problem of phase retrieval from magnitudes of STFT (short-time Fourier transform) measurements. The uniqueness of STFT phase retrieval had been established when the signal is one-dimensional function. In this article, we investigate the uniqueness of STFT phase retrieval when the signal is a two-dimensional vector function. And we prove the uniqueness theorem of STFT phase retrieval for bandlimited real-valued and complex-valued vector functions, respectively.